Embedded cooling method with configurability and replaceability for multi-chip electronic devices. (1st February 2022) - Zhang, Nan; Jiao, Binbin; Ye, Yuxin; Kong, Yanmei; Du, Xiangbin; Liu, Ruiwen; Cong, Bo; Yu, Lihang; Jia, Shiqi; Jia, Kunpeng
Highlights: Created a new type of embedded cooling modules for multi-chip electronic devices. The module can be reconfigured, and chips can be replaced multiple times. Tested a 70 × 88 × 9 mm 3 cooling module for a 3 × 3 array of chips. Demonstrated successful thermal management of multi-chip electronic devices. Can be useful for high-performance processors and DC/DC power converters. Abstract: Multi-chip thermal management technology is facing new challenges for improving system performance with the increasing use of multi-chip strategies in electronic systems. In this study, an embedded cooling method with configurability and replaceability for multi-chip electronic devices was demonstrated. A cooling module with the size of 70 × 88 × 9 mm 3 for a 3 × 3 chip array verified the feasibility. The experimental results showed that each chip was cooled independently with no thermal coupling between each other, the maximum temperature of the array less than 85.81 ℃ and the temperature uniformity was 0.0728 (coefficient of variation) at 600 W/cm 2 and 500 mL/min. Under the same conditions, the cooling effect of chips in the array was not affected by arrangements, where the differences in pressure drops and temperature uniformity were less than 4% and 0.0276, respectively. The heat dissipation effect of the chips in the module remained unchanged after repeated assembly, which proves the replaceability of the chips into the module. Therefore, this configurable and replaceable cooling method for multi-chip electronic devices is promising for high-performance processors and power converters.